Spectroscopic constraints on UV metal line emission at z ≃ 6–9: the nature of Lyα emitting galaxies in the reionization era. Issue 1 (22nd June 2018) - Mainali, Ramesh; Zitrin, Adi; Stark, Daniel P; Ellis, Richard S; Richard, Johan; Tang, Mengtao; Laporte, Nicolas; Oesch, Pascal; McGreer, Ian
ABSTRACT: Recent studies have revealed intense ultraviolet (UV) metal emission lines in a modest sample of $z$ > 7 Lyman-α emitters, indicating a hard ionizing spectrum is present. If such high ionization features are shown to be common, it may indicate that extreme radiation fields play a role in regulating the visibility of Lyα in the reionization era. Here, we present deep near-infrared spectra of seven galaxies with Lyα emission at 5.4 < $z$ < 8.7 (including a newly confirmed lensed galaxy at $z$ Lyα = 6.031) and three bright $z$ ≃ 7 photometric targets. In nine sources, we do not detect UV metal lines. However in the $z$ Lyα = 8.683 galaxy EGSY8p7, we detect a 4.6σ emission line in the narrow spectral window expected for N v λ1243. The feature is unresolved (FWHM < 90 km s −1 ) and is likely nebular in origin. A deep H -band spectrum of EGSY8p7 reveals non-detections of C iv, He ii, and O iii ]. The presence of N v requires a substantial flux of photons above 77 eV, pointing to a hard ionizing spectrum powered by an active galactic nucleus or fast radiative shocks. Regardless of its origin, the intense radiation field of EGSY8p7 may aid the transmission of Lyα through what is likely a partially neutral intergalactic medium. With this new detection, five of 13 known Lyα emitters at $z$ > 7 have now been shown to have intense UV line emission, suggesting that extreme radiation fields are commonplace among the Lyα population. Future observations with JWST will eventually clarify the origin of these features and explain their role in the visibility of Lyα in the reionization era.